Metagenomic pathogen sequencing in resource-scarce settings: Lessons learned and the road ahead - Yek, Christina; Pacheco, Andrea R.; Vanaerschot, Manu; Bohl, Jennifer A.; Fahsbender, Elizabeth; Aranda-Díaz, Andrés; Lay, Sreyngim; Chea, Sophana; Oum, Meng Heng; Lon, Chanthap; Tato, Cristina M.; Manning, Jessica E. (Frontiers in Epidemiology, 2022)
Metagenomic next-generation sequencing (mNGS) is the process of sequencing all genetic material in a biological sample. The technique is growing in popularity with myriad applications including outbreak investigation, biosurveillance, and pathogen detection in clinical samples. However, mNGS programs are costly to build and maintain, and additional obstacles faced by low- and middle-income countries (LMICs) may further widen global inequities in mNGS capacity. Over the past two decades, several important infectious disease outbreaks have highlighted the importance of establishing widespread sequencing capacity to support rapid disease detection and containment at the source. Using lessons learned from the COVID-19 pandemic, LMICs can leverage current momentum to design and build sustainable mNGS programs, which would form part of a global surveillance network crucial to the elimination of infectious diseases.